1993
DOI: 10.1063/1.464513
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of the reaction of atomic oxygen with silane

Abstract: The flash-photolysis resonance-fluorescence technique has been employed to measure the rate constant for O+SiH4+products from 295-565 K, and yielded kr = 1.23 X lo-" exp( -14.6 kJ mol-'/RT) cm3 s-r with an accuracy of about f 15%. The transition state for direct H-atom abstraction has been characterized at up to the Gaussian-2 ab initio level of theory. With small adjustments it is possible to model kinetic data for O+SiH, in terms of an abstraction channel leading to OH + SiH, . This agreement does not rule o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
26
1
Order By: Relevance
“…Details of the kinetic apparatus have been given elsewhere [16][17][18]. Briefly, SO 2 diluted in Ar bath gas flowed through a stainless steel reaction cell.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the kinetic apparatus have been given elsewhere [16][17][18]. Briefly, SO 2 diluted in Ar bath gas flowed through a stainless steel reaction cell.…”
Section: Methodsmentioning
confidence: 99%
“…The six best estimates of kl from Table 2 are plotted in Arrhenius form in Figure 1. A linear fit, where each point was weighted by the inverse variance, yields k l ( T ) = (6.7 f 2.0) X lo-'' X exp(-1030 f 100 K/T) cm3 molecule-' s-' (6) with E, = 8.6 f 0.8 kJ mol-'. Thequoted uncertainties represent f 2 u for A and E,.…”
Section: -12mentioning
confidence: 99%
“…The present data also extend the kinetic database for alkyl-substituted silanes and are discussed in the context of recent measurements on O(3P) reactions with triethylsilane and triisopropylsilane.I* Recently it was shown that k2 could be closely reproduced by combination of ab initio Gaussian-2 theory, which approximates QCISD(T)/6-31 l+G(3df,2p)//MP2/6-3lG* energies,I3 witha transition state theory (TST) analysis. 6 Here the analogous transition state for kl is too large to analyze at the same level of theory, so we assess the relative energetics of the transition states 0 Abstract published in Advance ACS Abstracts, March IS, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…The laser photolysis apparatus and general operating procedures have been described elsewhere [10][11][12][13]. Briefly, mixtures of H2S and CS2 diluted in Ar bath gas flowed slowly through a heated, stainless steel reaction cell.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%